2019
DOI: 10.1021/acsami.9b05718
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Friction Modifiers and Dispersants in Lubricants: The Case of Glycerol Monooleate and Polyisobutylsuccinimide-Polyamine

Abstract: The structural and frictional properties of 10 wt% solutions of the amphiphilic molecules glycerol monooleate (GMO) and polyisobutylsuccinimide-polyamine (PIBSA-PAM) in squalane are studied using molecular dynamics simulations in bulk and under confinement between iron-oxide surfaces. GMO is a friction modifier, PIBSA-PAM is a dispersant, and squalane is a good model for typical base oils. A range of liquid compositions and applied pressures is explored and the formation and stability of reverse micelles is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…In recent work, the interaction between OFMs and dispersants (used to keep soot in solution) has been studied in MD simulations, and some significant effects on friction have been uncovered. The results of this work (by two of the authors, GT and PJC) are currently being prepared for publication [66].…”
Section: Competition Between Adsorption and Self-assemblymentioning
confidence: 99%
“…In recent work, the interaction between OFMs and dispersants (used to keep soot in solution) has been studied in MD simulations, and some significant effects on friction have been uncovered. The results of this work (by two of the authors, GT and PJC) are currently being prepared for publication [66].…”
Section: Competition Between Adsorption and Self-assemblymentioning
confidence: 99%
“…The difference can be structural and/or chemical. As GMO and OA can form micelles in oil, [5][6][7] micellar layers, rather than OFM monolayers, may form on PAI. If the hydrolysis of GMO is pressure dependent, these layers may consist of mainly GMO, rather than OA, in PAI-PAI contacts due to its lower pressure.…”
Section: Effect Of Oleic Acidmentioning
confidence: 99%
“…It has been suggested that GMO, its hydrolysis products (oleic acid and glycerol), and water formed micelles or aggregates in n-heptane and toluene under both static and shear conditions. [5][6][7] These micelles adsorbed on the surface. The nature of the GMO adsorbed layer is surface dependent.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many simulation studies of the rheological properties of squalane, and these have mainly focused on the diffusion and (Newtonian) shear viscosity under ambient conditions, 24,25 the non-Newtonian (shear-thinning) regime at high pressure, [26][27][28] and the rheological and tribological properties of the confined fl uid, ei ther on it s ow n, [29][30][31] or with additives. 32,33 In the MD work by Porras-Vazquez et al, 18 referred to above and discussed in Section III A, the liquid-solid phase boundary was sketched out over the temperature range 235-500 K, and at pressures of up to about 5 GPa.…”
Section: Introductionmentioning
confidence: 99%